Don’t tell on me: Experimental evidence of asymmetric information in transnational households - Ambler, Kate (International Food Policy Research Institute, 2013)
Although most theoretical models of household decisionmaking assume perfect information, empirical studies suggest that information asymmetries can have large impacts on resource allocation. In this study, I demonstrate the importance of these asymmetries in transnational households, where physical distance between family members can make information barriers especially acute.